Estudos bioquímicos e moleculares de genes de trichoderma envolvidos no mecanismo de micoparasitismo - Siqueira, Saulo José Linhares de (2012)
Species of Trichoderma are commercially applied as biological control agents and are antagonists of important plant pathogenic fungi (as Rhizoctonia, Sclerotinia and Fusarium species) due to its mycoparasitic characteristics. Research has been performed to have a better comprehension of molecular aspects of the biocontrol mechanisms performed by Trichoderma and to find isolates with high antagonistic potential against plant pathogens. In the present study the expression of mycoparasitism-related genes was performed T. asperellum T00 and T. harzianum ALL42 (Enzimologia group ICB/UFG fungal collection) that have great potential as biocontrol agent. Each chapter of this work refers to one of the species studied. In Chapter 1 T. asperellum isolate T00, known to produce high levels of cell wall degrading enzymes, has its β-1,3-glucanases enzymes and genes (tag83 and tag27) studied. The gene tag27 was cloned and characterized and codes to an 27kDa endo-β-1,3glucanase with and 285 aminoacids and 96% similar to a glucanases from T.atroviride. The enzyme was detected when T. asperellum was grown in Rhizoctonia solani or Sclerotinia sclerotiorum cell wall-containing media but not in Fusarium oxysporum cell wall-containing media. The tag83 and tag27 genes was repressed in media containing glucose as carbon source and upregulated in cell wall containing media and during plate confrontation tests with pathogenic fungi. Chapter 2 shows T. harzianum isolate ALL42 genes involved in mycoparasitism against R. solani or S. sclerotiorum detected using subtractive hybridization approach. T. harzianum was grown with R. solani or S. sclerotiorum cell wall as carbon source and the RNA used both as tester and driver in each of two subtractive library constructed. Sequencing analysis resulted in 47 genes related with growth in R. solani cell wall media and 114 genes related with growth in S. sclerotiorum cell wall media. To confirm the obtained data, 18 genes were tested by quantitative real time RT-PCR and 9 were differentially expressed in the same condition of the library they were detected. Five of these genes were also differentially expressed during plate confrontation assay with the respective pathogen, two of them expressed during contact with R. solani (cutinase and alginate lyase) and 3 during contact with S. sclerotiorum (hsp98, serin endopeptidase and a hypotetic gene). The results presented in this study provides additional information about the role of 1,3glucanase genes in mycoparasitism and of other genes related to antagonism against specific pathogens, providing helpful insights in the mechanism of biocontrol performed by Trichoderma.